Trade policy reforms under adjustment programes (IBRD Washington, D.C.US, 1992)
Reviews the Bank's experience in support of trade policy reform during the 1980s in a number of developing countries including Jamaica. Focusses on the Bank's operations and related issues in adjustment lending. Assesses whether trade policy reforms were complemented by other measures including macroeconomic, industrial and financial policies.
DC